2007
DOI: 10.1111/j.1574-6941.2006.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of sponge-associated bacteria in the Mediterranean sponge Tethya aurantium

Abstract: The local distribution of the bacterial community associated with the marine sponge Tethya aurantium Pallas 1766 was studied. Distinct bacterial communities were found to inhabit the endosome and cortex. Clear differences in the associated bacterial populations were demonstrated by denaturing gradient gel electrophoresis (DGGE) and analysis of 16S rRNA gene clone libraries. Specifically associated phylotypes were identified for both regions: a new phylotype of Flexibacteria was recovered only from the sponge c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 51 publications
7
90
0
Order By: Relevance
“…These biased light regimes are preferable for the predominantly R-phycoerythrin type-B and type-C photosymbionts. In some marine sponges, a similar spatial segregation of multiple photosymbiont species has been reported (Thiel et al, 2007). The co-existence of multiple photosymbiotic species is not commonly found in the photosymbiotic didemnid ascidians.…”
Section: Discussionsupporting
confidence: 62%
“…These biased light regimes are preferable for the predominantly R-phycoerythrin type-B and type-C photosymbionts. In some marine sponges, a similar spatial segregation of multiple photosymbiont species has been reported (Thiel et al, 2007). The co-existence of multiple photosymbiotic species is not commonly found in the photosymbiotic didemnid ascidians.…”
Section: Discussionsupporting
confidence: 62%
“…The analysis of 16S rRNA genes through clone libraries and fingerprinting approaches such as denaturing gradient gel electrophoresis (DGGE) has greatly extended our knowledge about the phylogenetic richness of sponge-associated bacteria and archaea (Webster et al, 2001(Webster et al, , 2004Hentschel et al, 2002;Taylor et al, 2004Taylor et al, , 2007bHolmes and Blanch, 2006;Longford et al, 2007;Schmitt et al, 2007Schmitt et al, , 2008Thiel et al, 2007;Mohamed et al, 2008b;Zhu et al, 2008). Researchers in other systems have taken this approach one step further, yielding insights into both richness and activity by comparing 16S rRNA gene-and 16S rRNA-derived sequences, respectively (Moeseneder et al, , 2005Winter et al, 2001;Troussellier et al, 2002;Mills et al, 2005;Gentile et al, 2006;Martinez et al, 2006;Brinkmann et al, 2008;McIlroy et al, 2008;West et al, 2008;Rodriguez-Blanco et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of spatial heterogeneity observed for coral-associated microbes in this study is similar to patterns observed for a variety of other host-associated microbial communities. Sponges are another example of benthic, sessile metazoa that contain a diverse bacterial assemblage throughout their ultrastructure (Thiel et al 2007). A denaturing gradient gel electrophoresis (DGGE) survey of bacterial communities in multiple samples from 2 marine sponges Cymbastela concentric and Callyspongia sp.…”
mentioning
confidence: 99%